Особливості перекладу англійських фразеологічних одиниць у політичному дискурсі - Бєлих, Д. І.; Ковальова, Євгенія Ігорівна (НТУ "ХПІ", 2018)
У статті проаналізовано проблеми перекладу англійських фразеологічних одиниць, описано особливості їх трансформації українською мовою. Проаналізовано основні способи перекладу фразеологізмів в політичному дискурсі, а саме описовий спосіб, повний еквівалент, частковий еквівалент, калькування. Наведено основні рекомендації щодо способів перекладу англійських фразеологізмів. Охарактеризовано поняття політичний дискурс та виявлені головні його особливості. Проаналізовано сенсове навантаження фразеологізмів політичного дискурсу, що зумовлює необхідність їх адекватного перекладу засобами української мови.

This article is concerned with burning issues of studying phraseological units, used in publicistic periodicals, such as The Guardian, The Independent, Times, Financial Times, and also in video records of political trend. The article analyzes the problems of the translation of English phraseological units, describes the peculiarities of their transformation into the Ukrainian language. The basic ways of the translation of phraseological units in political discourse are analyzed, namely: descriptive method, full equivalent, partial equivalent, tracing. The main recommendations on how to translate English phraseological units are given. The concept of political discourse is characterized and its main features a re revealed. The content on political phraseological units are analyzed, which necessitates their adequate translation into the Ukrainian language.
Translation features of english phraseological units in the political discourse
Keywords: описовий спосіб перекладу; повний еквівалент; частковий еквівалент; калькування; адекватний переклад; descriptive translation method; full equivalent; partial equivalent